2001
DOI: 10.1159/000055711
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of the Neck in Thyroid Cancer

Abstract: Thyroid cancer is a relatively common clinical problem. The American Cancer Society has estimated 1,050,000 newly diagnosed cancers in 1999 in the United States, of which 16,000 are expected to be of thyroid origin. Although most thyroid cancers have an excellent prognosis as compared with other malignant tumors, it is estimated that approximately 1,225 deaths will be attributed to the disease [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the low-risk group, the survival was 99%, while in the intermediate-and highrisk groups it was 87 and 57%, respectively. The understanding of the risk groups and prognostic factors appears to be extremely important in the biology and management of thyroid cancer, especially related to the extent of thyroidectomy [16] and adjuvant forms of therapy.…”
Section: Prognostic Factors and Risk Group Analysismentioning
confidence: 99%
“…In the low-risk group, the survival was 99%, while in the intermediate-and highrisk groups it was 87 and 57%, respectively. The understanding of the risk groups and prognostic factors appears to be extremely important in the biology and management of thyroid cancer, especially related to the extent of thyroidectomy [16] and adjuvant forms of therapy.…”
Section: Prognostic Factors and Risk Group Analysismentioning
confidence: 99%
“…Another unique feature of thyroid cancer is that nodal metastasis has no prognostic bearing (12,32), whereas in other human cancers (e.g. of the lung, head and neck or colon) it reduces the survival rate by : 50%.…”
Section: Diagnosismentioning
confidence: 99%
“…Recently, with the introduction of thyroglobulin monitoring during follow-up, an increasing number of patients with rising thyroglobulin levels have been detected, related mainly to metastatic disease to the lymph nodes. An extended selective neck dissection is generally recommended for such patients if neck ultrasound and ultrasound-guide d ne-needle biopsy con rm metastatic disease to the neck lymph nodes (32). The internal jugular vein, spinal accessory nerve and sternocleidomastoi d muscle should only be sacri ced if they are affected by gross disease.…”
Section: Diagnosismentioning
confidence: 99%
“…Although some studies have shown that the presence of LN metastases does not alter survival, [1][2][3] other studies have shown that PTC recurrence increases morbidity and mortality and that the presence of cervical LN metastasis at diagnosis is the single most important factor that ultimately increases the risk of local recurrence.…”
mentioning
confidence: 99%